2021
DOI: 10.1080/1046560x.2021.1873549
|View full text |Cite|
|
Sign up to set email alerts
|

Supporting Equity in Virtual Science Instruction Through Project-Based Learning: Opportunities and Challenges in the Era of COVID-19

Abstract: Project-based learning (PBL) is a long-standing curricular model that has been argued to support equity-based goals in science learning. Yet, little is known about how PBL can be implemented effectively and equitably in the context of virtual instruction. This comparative case study follows two elementary science teachers as they transition to virtual instruction at the beginning of the COVID-19 pandemic. Drawing from classroom observations and interview data, we highlight the opportunities and challenges of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
1
23
0
2
Order By: Relevance
“…As a result, students must actively participate in the teaching and learning process. Entrepreneurship is an example of a course that requires tight collaboration between students and lecturers [5]. One of several objectives of entrepreneurship in higher education is the ability to analyze and solve problems that are more authentic and concrete than the material presented by lecturers in class; additionally, students receive both soft and hard skill learning, implying that they have knowledge of entrepreneurial concepts and principles as well as the skills to develop them.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, students must actively participate in the teaching and learning process. Entrepreneurship is an example of a course that requires tight collaboration between students and lecturers [5]. One of several objectives of entrepreneurship in higher education is the ability to analyze and solve problems that are more authentic and concrete than the material presented by lecturers in class; additionally, students receive both soft and hard skill learning, implying that they have knowledge of entrepreneurial concepts and principles as well as the skills to develop them.…”
Section: Introductionmentioning
confidence: 99%
“…Any learning approach based on Problem Based Learning contributes a lot in improving knowledge in the field of learning [8]. [5] found that combining the Problem Based Learning model can help students solve and explore critical thinking skills, their interest in addressing learning challenges and enhance students' entrepreneurial achievement.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations